Hubungan Kebutuhan terhadap Informasi dengan Tingkat Kecemasan Pasien Pra-Operasi di Ruang Rawat Bedah RSUD Goeteng Taroenadibrata Purbalingga - Iwan Purnawan; Arif Imam Hidayat; Dani Tri Santosa; Wiwit Rita Suprilatin (Journal of Bionursing, 2021)
Background. Surgery is a complex procedure that is frightening to most patients. This could be a stressor that could harm the patient. One of the causes of anxiety is the curiosity of the patient about the surgical process they are going to experience. The objective of this study is to determine the relationship between the level of information needs and anxiety of preoperative patients. Methods. This research is a type of cross-sectional analytical survey conducted to investigate the relationship between the level of knowledge and the level of anxiety in preoperative patients at Goeteng Taroenadibrata Purbalingga Hospital. The anxiety measuring instrument used is the APAIS (Amsterdam Preoperative Anxiety and Information Scale) which has been translated and passed the validation and reliability tests. The statistical test uses the gamma correlation test to determine the relationship between the level of information needs and the level of anxiety. Results. Most of the respondents had a moderate level of anxiety of 58.5 per cent (n=41). The majority of respondents' information needs on the surgical process are at a moderate level (63.4 percent ). There is a significant relationship between the level of information needs and anxiety of preoperative patients (p = 0.001 and r = 0.92).. Conclusion. The higher the level of the patient's need for information, the higher the level of anxiety experienced.